Efeito temporal na parasitofauna do bagre invasor Trachelyopterus galeatus (Linnaeus, 1766) de uma planície Neotropical. - Michelan, Gabriela (2022)
Aquatic environments have been anthropically influenced over the years, mainly with the construction of dams and hydroelectric plants. However, few studies evaluate how the parasitic fauna can be influenced in the long term by these environmental changes. Possible changes in the composition of endoparasites of the invasive fish Trachelyopterus galeatus in the upper Paraná River floodplain were investigated over a 27-year study period. 79 fish were analyzed in period 1 (1993) and 31 in period 2 (2019/2020). In the first period, the fish showed higher values in the variables weight (g) and standard length (cm), when compared to period 2. A total of five species of endoparasites were found, three per period. Although the richness was the same, the composition of endoparasites differed between the periods, as only one species of digenetic (Microrchis oligovitellum) parasitized the host in both periods of study. It was found that both the development of the fish and its endoparasites were affected over time. It is noteworthy that the beginning of operation of the Porto Primavera dam, located upstream of the plain, occurred between the two sampling periods (1999), and caused several environmental changes, possibly being the main responsible for these changes in the parasitofauna. Most endoparasites require intermediate hosts to complete their life cycles. Therefore, a modified environment may lose diversity and ecological interactions, as it affects the populations they use during the transmission process between hosts. This may explain the difference found in the infracommunities of T. galeatus parasites, emphasizing, through the results obtained, the importance of including these organisms in studies that evaluate environmental impacts caused by anthropic actions.